2021
DOI: 10.3389/fpsyt.2021.636706
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Male Strength Athletes Who Use Non-prescribed Anabolic-Androgenic Steroids

Abstract: Background: One sub-population potentially affected by the COVID-19 pandemic are strength athletes who use anabolic-androgenic steroids (AAS). We examined links between disruption in AAS use and training due to the pandemic and mental health outcomes in this population, hypothesising: (a) the pandemic would be linked with reduced training and AAS use; and (b) athletes perceiving greater impact on their training and AAS use would report increases in detrimental mental health outcomes.Methods: Male strength athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 83 publications
(103 reference statements)
1
14
0
Order By: Relevance
“…The physical activity, subjective training intensity and subjective performance of BoFA dropped significantly during lockdown. The drop from pre-lockdown values in physical activity, subjective training intensity and performance is plausible and is in line with other research that has been published on the effects of the lockdown on this particular population (Zoob Carter et al, 2021 ). This represents a pattern similar to other studies, which reported a reduced training frequency, shorter training sessions and lower sport-specific intensity in many other sports (Washif et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The physical activity, subjective training intensity and subjective performance of BoFA dropped significantly during lockdown. The drop from pre-lockdown values in physical activity, subjective training intensity and performance is plausible and is in line with other research that has been published on the effects of the lockdown on this particular population (Zoob Carter et al, 2021 ). This represents a pattern similar to other studies, which reported a reduced training frequency, shorter training sessions and lower sport-specific intensity in many other sports (Washif et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In another study, it was suggested that COVID-19 risks could be reduced in the elderly by hormone replacement therapy (estrogen and testosterone) due to the anti-inflammatory actions of sex hormones and the anabolic actions of testosterone [ 22 ]. Another study showed that the COVID-19 pandemic had clearly affected the use of AAS by reducing AAS doses and training frequency as compared to pre-pandemic [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the specific nature of COVID-19 characteristically elicits immune responses that can lead to hyperinflammation, we took the position – from a suppositional basis – that the use of androgen could conceivably accelerate, exacerbate, or even initiate significantly more dangerous responses to COVID-19. Of note, whilst at the time of press, there was some emerging anecdotal and journalistic evidence, there were no widely available case studies or peer reviewed resources that had clearly demonstrated a link between androgen use and increased risk of mortality or disease severity from COVID-19, as well as associated mental health challenges [ 25 ].…”
Section: Androgen Use and Potential Problems With Coronavirus Disease 2019mentioning
confidence: 99%